2008
DOI: 10.1111/j.1365-2966.2008.13522.x
|View full text |Cite
|
Sign up to set email alerts
|

Model-based pattern speed estimates for 38 barred galaxies

Abstract: We have modelled 38 barred galaxies by using near-IR and optical data from the Ohio State University Bright Spiral Galaxy Survey. We constructed the gravitational potentials of the galaxies from $H$-band photometry, assuming constant mass-to-light ratio. The halo component we chose corresponds to the so called universal rotation curve. In each case, we used the response of gaseous and stellar particle disc to rigidly rotating potential to determine the pattern speed. We find that the pattern speed of the bar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
146
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(176 citation statements)
references
References 106 publications
23
146
3
1
Order By: Relevance
“…Contopoulos (1980) studied how a galaxy responds to the barred perturbations of density, and he concluded that the bar corotation should be found close to the end of the bar, and in principle, the value of the rotational parameter should be quite close to but larger than 1. This general conclusion has since been supported in diverse publications, both theoretical and observational (Athanassoula 1992;Valenzuela & Klypin 2003;Rautiainen et al 2008;Buta & Zhang 2009;Font et al 2014a;Aguerri et al 2015). As described in a former section, we give the two limits for the bar length, consequently, we calculate the two limits for the  parameter, the values of this parameter appearing in Table 2, Column 7, are the calculated as the mean of the two limits.…”
Section: The Scaled Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Contopoulos (1980) studied how a galaxy responds to the barred perturbations of density, and he concluded that the bar corotation should be found close to the end of the bar, and in principle, the value of the rotational parameter should be quite close to but larger than 1. This general conclusion has since been supported in diverse publications, both theoretical and observational (Athanassoula 1992;Valenzuela & Klypin 2003;Rautiainen et al 2008;Buta & Zhang 2009;Font et al 2014a;Aguerri et al 2015). As described in a former section, we give the two limits for the bar length, consequently, we calculate the two limits for the  parameter, the values of this parameter appearing in Table 2, Column 7, are the calculated as the mean of the two limits.…”
Section: The Scaled Propertiesmentioning
confidence: 99%
“…For a review of these used until 2008 we refer to Rautiainen et al (2008). Here we list some of the most representative methods, some of which measure the pattern speed of the bar, while others determine the corotation radius directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bars with RCR/R bar > 3.0 are very rare in nature. Only one is found in the compilation made by Rautiainen et al (2008), with R = 3.43 ± 0.95, and even in that case the error may still place the value below the limit of 3.0. For this reason, we have discarded those simulations in which corotation radius is more than three times the bar radius.…”
Section: Dynamical Simulationsmentioning
confidence: 99%
“…Associating a ring in a barred galaxy with the location of a major resonance with the bar (Buta & Combes 1996) yields, with kinematic information, an estimate of the pattern speed. Rautiainen et al (2008) computed models of the stellar and gas (sticky particles) responses to forcing by photometric models of 38 barred galaxies, in which they assumed that the entire non-axisymmetric structure rotated at the same pattern speed. They attempted to match the model to the visual morphology of the galaxy, and found a range of values for R. However, in most cases where R ≫ 1, the fit is dominated by the outer spiral, which may have a lower angular speed than does the bar.…”
Section: Bar Pattern Speedsmentioning
confidence: 99%